107k views
1 vote
Evaluate f′ (1) and f′′ (1): = x√x

--------

3√ 5

User Tony Bao
by
4.9k points

1 Answer

8 votes

Answer:


\displaystyle f'(1) = (3)/(2)


\displaystyle f''(1) = (3)/(4)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra II

  • Exponential Rule [Rewrite]:
    \displaystyle b^(-m) = (1)/(b^m)
  • Exponential Rule [Root Rewrite]:
    \displaystyle \sqrt[n]{x} = x^{(1)/(n)}

Calculus

Derivatives

Derivative Notation

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Derivative Property [Addition/Subtraction]:
\displaystyle (d)/(dx)[f(x) + g(x)] = (d)/(dx)[f(x)] + (d)/(dx)[g(x)]

Derivative Rule [Product Rule]:
\displaystyle (d)/(dx) [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)

Derivative Rule [Quotient Rule]:
\displaystyle (d)/(dx) [(f(x))/(g(x)) ]=(g(x)f'(x)-g'(x)f(x))/(g^2(x))

Explanation:

Step 1: Define

f(x) = x√x

f'(1) is x = 1 for 1st derivative

f''(1) is x = 1 for 2nd derivative

Step 2: Differentiate

  1. [1st Derivative] Product Rule:
    \displaystyle f'(x) = (d)/(dx)[x]√(x) + x(d)/(dx)[√(x)]
  2. [1st Derivative] Rewrite [Exponential Rule - Root Rewrite]:
    \displaystyle f'(x) = (d)/(dx)[x]√(x) + x(d)/(dx)[x^{(1)/(2)}]
  3. [1st Derivative] Basic Power Rule:
    \displaystyle f'(x) = (1 \cdot x^(1 - 1))√(x) + x((1)/(2)x^{(1)/(2)-1})
  4. [1st Derivative] Simply Exponents:
    \displaystyle f'(x) = (1 \cdot x^0)√(x) + x((1)/(2)x^{(-1)/(2)})
  5. [1st Derivative] Simplify:
    \displaystyle f'(x) = √(x) + x((1)/(2)x^{(-1)/(2)})
  6. [1st Derivative] Rewrite [Exponential Rule - Rewrite]:
    \displaystyle f'(x) = √(x) + x(\frac{1}{2x^{(1)/(2)}})
  7. [1st Derivative] Rewrite [Exponential Rule - Root Rewrite]:
    \displaystyle f'(x) = √(x) + x((1)/(2√(x)))
  8. [1st Derivative] Multiply:
    \displaystyle f'(x) = √(x) + (x)/(2√(x))
  9. [2nd Derivative] Rewrite [Exponential Rule - Root Rewrite]:
    \displaystyle f'(x) = x^{(1)/(2)} + \frac{x}{2x^{(1)/(2)}}
  10. [2nd Derivative] Basic Power Rule/Quotient Rule [Derivative Property]:
    \displaystyle f''(x) = (1)/(2)x^{(1)/(2) - 1} + \frac{(d)/(dx)[x](2x^{(1)/(2)}) - x(d)/(dx)[2x^{(1)/(2)}]}{(2x^{(1)/(2)})^2}
  11. [2nd Derivative] Simplify/Evaluate Exponents:
    \displaystyle f''(x) = (1)/(2)x^{(-1)/(2)} + \frac{(d)/(dx)[x](2x^{(1)/(2)}) - x(d)/(dx)[2x^{(1)/(2)}]}{4x}
  12. [2nd Derivative] Rewrite [Exponential Rule - Rewrite]:
    \displaystyle f''(x) = \frac{1}{2x^{(1)/(2)}} + \frac{(d)/(dx)[x](2x^{(1)/(2)}) - x(d)/(dx)[2x^{(1)/(2)}]}{4x}
  13. [2nd Derivative] Basic Power Rule:
    \displaystyle f''(x) = \frac{1}{2x^{(1)/(2)}} + \frac{(1 \cdot x^(1 - 1))(2x^{(1)/(2)}) - x((1)/(2) \cdot 2x^{(1)/(2) - 1})}{4x}
  14. [2nd Derivative] Simply Exponents:
    \displaystyle f''(x) = \frac{1}{2x^{(1)/(2)}} + \frac{(1 \cdot x^0)(2x^{(1)/(2)}) - x((1)/(2) \cdot 2x^{(-1)/(2)})}{4x}
  15. [2nd Derivative] Simplify:
    \displaystyle f''(x) = \frac{1}{2x^{(1)/(2)}} + \frac{2x^{(1)/(2)} - x((1)/(2) \cdot 2x^{(-1)/(2)})}{4x}
  16. [2nd Derivative] Multiply:
    \displaystyle f''(x) = \frac{1}{2x^{(1)/(2)}} + \frac{2x^{(1)/(2)} - x(x^{(-1)/(2)})}{4x}
  17. [2nd Derivative] Rewrite [Exponential Rule - Rewrite]:
    \displaystyle f''(x) = \frac{1}{2x^{(1)/(2)}} + \frac{2x^{(1)/(2)} - x(\frac{1}{x^{(1)/(2)}})}{4x}
  18. [2nd Derivative] Multiply:
    \displaystyle f''(x) = \frac{1}{2x^{(1)/(2)}} + \frac{2x^{(1)/(2)} - \frac{x}{x^{(1)/(2)}}}{4x}
  19. [2nd Derivative] Simplify:
    \displaystyle f''(x) = \frac{1}{2x^{(1)/(2)}} + \frac{x^{(1)/(2)}}{4x}
  20. [2nd Derivative] Rewrite [Exponential Rule - Root Rewrite]:
    \displaystyle f''(x) = (1)/(2√(x)) + (√(x))/(4x)

Step 3: Evaluate

  1. [1st Derivative] Substitute in x:
    \displaystyle f'(1) = √(1) + (1)/(2√(1))
  2. [1st Derivative] Evaluate Roots:
    \displaystyle f'(1) = 1 + (1)/(2(1))
  3. [1st Derivative] Multiply:
    \displaystyle f'(1) = 1 + (1)/(2)
  4. [1st Derivative] Add:
    \displaystyle f'(1) = (3)/(2)
  5. [2nd Derivative] Substitute in x:
    \displaystyle f''(1) = (1)/(2√(1)) + (√(1))/(4(1))
  6. [2nd Derivative] Evaluate Roots:
    \displaystyle f''(1) = (1)/(2(1)) + (1)/(4(1))
  7. [2nd Derivative] Multiply:
    \displaystyle f''(1) = (1)/(2) + (1)/(4)
  8. [2nd Derivative] Add:
    \displaystyle f''(1) = (3)/(4)
User Chaonextdoor
by
5.6k points